Structure of the pneumococcal l, d‐carboxypeptidase DacB and pathophysiological effects of disabled cell wall hydrolases DacA and DacB. Issue 6 (14th August 2014) - Abdullah, Mohammed R.; Gutiérrez‐Fernández, Javier; Pribyl, Thomas; Gisch, Nicolas; Saleh, Malek; Rohde, Manfred; Petruschka, Lothar; Burchhardt, Gerhard; Schwudke, Dominik; Hermoso, Juan A.; Hammerschmidt, Sven
Summary Bacterial cell wall hydrolases are essential for peptidoglycan turnover and crucial to preserve cell shape. The d, d‐carboxypeptidase DacA and l, d‐carboxypeptidase DacB of Streptococcus pneumoniae function in a sequential manner. Here, we determined the structure of the surface‐exposed lipoprotein DacB. The crystal structure of DacB, radically different to that of DacA, contains a mononuclear Zn2+ catalytic centre located in the middle of a large and fully exposed groove. Two different conformations were found presenting a different arrangement of the active site topology. The critical residues for catalysis and substrate specificity were identified. Loss‐of‐function of DacA and DacB altered the cell shape and this was consistent with a modified peptidoglycan peptide composition in dac mutants. Contrary, an lgt mutant lacking lipoprotein diacylglyceryl transferase activity required for proper lipoprotein maturation retained l, d‐carboxypeptidase activity and showed an intact murein sacculus. In addition we demonstrated pathophysiological effects of disabled DacA or DacB activities. Real‐time bioimaging of intranasal infected mice indicated a substantial attenuation of ΔdacB and ΔdacAΔdacB pneumococci, while ΔdacA had no significant effect. In addition, uptake of these mutants by professional phagocytes was enhanced, while the adherence to lung epithelial cells was decreased. Thus, structural and functional studies suggest DacA and DacB as optimal drug targets.